Objetos virtuales de aprendizaje como estrategia didáctica de enseñanza de la matemática en estudiantes de primero de bachillerato del colegio Bernardo Dávalos León”, septiembre- diciembre de 2020 - Ibarra Berrones, Elena del Rocío (2021)
ABSTRACT This project aimed to use virtual learning items as a didactic strategy to support the mathematics teaching process in the First High School level of "Bernardo Davalos León" School, in September-December 2020. It is known that the use of virtual learning objects (OVA) is essential, as a didactic teaching strategy to encourage learning, since it was evidenced the lack of knowledge in the teachers of the management of suggested tools such as Ardora, JClic, HotPotatoes, eXeLearning, Nearpod, Genially and Educaplay due to outdated knowledge of technological resources. A quantitative approach was adopted, with a non-experimental design, as descriptive in scope, propositional in the objective, field location, and cross-sectional time. A validity process of the instruments was developed by experts to have a greater degree of reliability in the inquiry, obtaining the qualification of "Excellent." The study was carried out in a non-probabilistic and intentional sample of 18 students in the first year of the Unified General High School. Data were collected through surveys and an interview. In addition, in the questionnaire results, especially in the category "Learning Activities," it was found that both teachers and students do not know the term OVA; therefore, these resources are not frequently used in the development of the class. In addition, it was concluded that OVA is necessary to innovate the teaching process; therefore, it is recommended that teachers be trained in using technological tools. Finally, it was established as a solution, the proposal of a manual for the teacher, in which it is oriented how to build OVA in the tools mentioned above, then implemented within the Moodle Platform based on the ADDIE Model. Keywords: Virtual learning objects, didactic strategy, teaching, ADDIE methodology, virtual environment. Reviewed by: Mgs. Lorena Solís Viteri ENGLISH PROFESSOR c.c. 0603356783